X‐ray CT and histological imaging of xylem vessels organization in Mimosa pudica. Issue 11 (12th September 2013) - Lee, Sang Joon; Song, Kahye; Kim, Hae Koo; Park, Joonghyuk
ABSTRACT Mimosa pudica has three distinct specialized organs, namely, pulvinus, secondary pulvinus, and pulvinule, which are respectively controlling the movements of petioles, leaflets, and pinna in response to external stimuli. Water flow is a key factor for such movements, but detailed studies on the organization of the vascular system for water transport in these organs have not been published yet. In this study, organizations of the xylem vessels and morphological features of the pulvinus, the secondary pulvinus, and the pulvinule were experimentally investigated by X‐ray computed tomography and histological technique. Results showed that the xylem vessels were circularly distributed in the specialized motile organs and reorganized into distinct vascular bundles at the extremities. The number and the total cross‐sectional area of the xylem vessels were increased inside the specialized motile organs. Morphological characteristics obtained in this study provided new insight to understand the functions of the vascular networks in the dynamic movements of M. pudica. Microsc. Res. Tech. 76:1204–1212, 2013. © 2013 Wiley Periodicals, Inc.